Exploring Adolescent Ideas for Designing Reproductive Health Interventions to Prevent Early Marriage and Adolescent Pregnancy - Adelina Fitri; Vinna Rahayu Ningsih; Marta Butar Butar; Erny Kusdiah; Ashar Nuzulul Putra; La Ode Reskiaddin (Universitas Islam Negeri Sumatera Utara, Medan, 2026)
Adolescence is a transitional phase filled with challenges, characterized by social development, attraction to the opposite sex, and vulnerability to risky behaviors. Adolescent pregnancy and early marriage remain global issues, including in Indonesia. Contributing factors include poverty, low levels of education, and inherited cultural practices. These lead to serious consequences such as school dropout, limited educational opportunities, and reduced quality of life, hindering the achievement of Indonesia Emas 2045. This study aims to explore adolescents’ ideas and perspectives regarding existing policies and to design potential interventions. This research employed a qualitative, interpretative approach. The study involved 24 undergraduate students from the Public Health Study Program, Universitas Jambi. Data were collected through Focus Group Discussions (FGDs) and in-depth interviews, analyzed using data reduction, and conclusion drawing. The research findings identified a significant knowledge gap regarding the availability of adolescent-specific reproductive health services (RHS) at universities and health facilities. Although most informants had adequate knowledge about adolescent pregnancy, many were not sufficiently aware of reproductive health services or counseling specifically targeting them. Informants also reported relatively good communication with their parents, particularly with mothers, while community figures were identified as playing important roles. Young people expect the availability of adolescent-focused health services, more effective communication with parents, especially greater involvement of fathers, and forums bringing together community leaders and adolescents to strengthen preventive efforts.